Python artificial intelligence projects : build 9 practical real-world AI projects to encounter common challenges using TensorFlow and Keras /: build 9 practical real-world AI projects to encounter common challenges using TensorFlow and Keras. (2018) - Pattanayak, Santanu
No abstract available